Pemahaman Organisasi HMI Terhadap Sikap Toleransi Beragama dalam Mencegah Terjadinya Sikap Intoleran Berdasarkan Perspektif Nilai Sila Persatuan Indonesia Di Fakultas Ekonomi Universitas Negeri Medan - Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; Saragih, Desvita; Purba, Nadia Divani (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2024)
Religious Organizations' Understanding of Religious Tolerance in Preventing Intolerant Attitudes Based on the Value Perspective of the Principles of Indonesian Unity refers to an analysis of the level of understanding that religious organizations have regarding religious tolerance. An attitude of religious tolerance is a behavioral attitude that respects and understands religious diversity in society. This understanding is important to prevent intolerant attitudes, which are rejection or dislike of religious diversity. This research uses a qualitative descriptive approach, with interviews as a data source. The research sample consisted of 10 respondents who were active members of HMI at the Faculty of Economics, Medan State University. This research aims to expand an in-depth understanding of how HMI understands the concept of religious tolerance and the efforts made to prevent intolerant attitudes, taking into account the values ​​of Indonesian unity.